2020
DOI: 10.1007/s13644-020-00396-0
|View full text |Cite
|
Sign up to set email alerts
|

Race, Religion and Support for the Affordable Care Act

Abstract: Using Pew Research Center's Voter Attitudes Survey from 2012, we assess the impact race has on the relationship between religious faith and worship attendance with support for the Affordable Care Act (ACA). We find that White Evangelicals, independent of partisan affiliation and social-demographic characteristics, are more likely than White Non-Evangelicals to reject the ACA. In addition, among Whites, support for the ACA weakens with increasing religious attendance, suggesting that responses to this law are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In looking at Black clergy within historically Black Protestant denominations McDaniel (2003) found that the more theologically conservative Church of God in Christ and liberal African Methodist Episcopal clergy were equally likely to support universal government-provided healthcare. Similarly, Franz and Brown (2020) find that among Whites, individuals that attended worship services more often and affiliated with Evangelical Protestant denominations were more likely than others to oppose Obamacare. In contrast, worship attendance and religious affiliation were unrelated to how Blacks and Hispanic felt about that policy.…”
Section: Race Religion and Political Attitudesmentioning
confidence: 81%
“…In looking at Black clergy within historically Black Protestant denominations McDaniel (2003) found that the more theologically conservative Church of God in Christ and liberal African Methodist Episcopal clergy were equally likely to support universal government-provided healthcare. Similarly, Franz and Brown (2020) find that among Whites, individuals that attended worship services more often and affiliated with Evangelical Protestant denominations were more likely than others to oppose Obamacare. In contrast, worship attendance and religious affiliation were unrelated to how Blacks and Hispanic felt about that policy.…”
Section: Race Religion and Political Attitudesmentioning
confidence: 81%
“…Research on White Evangelicals’ opinions on racial and socioeconomic inequality often find a resistance to the ideas of structural solutions to racial inequality (Brown 2009; Cobb, Perry, and Dougherty 2015; Elisha 2011). Evangelicals are not completely unwilling to acknowledge the importance of structures in social life, though they will often describe large organizations (especially the government) as more a source of problems than potential solutions (Franz and Brown 2020). This normative commitment is reflected in a tendency to emphasize individual solutions to structural problems.…”
Section: Introductionmentioning
confidence: 99%